Investigation of omeprazole stability in oral suspensions for pediatric use prepared extemporaneously from omeprazole capsules - Milić Jela; Radojković Branko; Jančić-Stojanović Biljana; Drašković Jasmina; Mirašević Slavica; Čalija Bojan (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
In this paper, a study exploring the stability of omeprazole in pediatric suspensions is presented. In order to determine the most suitable suspension, three different formulations were prepared and stored under refrigerated conditions and at room temperature for 30 days. Contents of omeprazole and preservatives were determined by liquid chromatographic method. Obtained results demonstrate that the vehicle consisting of: xanthan gum 0.3%, sodium bicarbonate 8%, Compound hydroxybenzoate solution APF 1% and purified water to 100% could have a significant potential in the development of a suitable omeprazole oral liquid for pediatric use. Namely, the content of omeprazole in the suspension prepared with this vehicle remained within acceptable range during the 30-day period, when stored refrigerated (2-8°C).